СТОК НАНОСОВ И УСЛОВИЯ ФОРМИРОВАНИЯ РУСЕЛ РЕК БАССЕЙНА СЕВЕРНОЙ ДВИНЫ - Резников П.Н.; Чалов Р.С. (My University, 2005)
Sediment run-off is postulated to be one of the main factors of channel processes, but detailed formulation of this state-ment is absent. The lack of reliable data on bedloacl sediments is but the least reason for this deficiency. The paper presents data, filling up this gap and considers the correlation between sediment run-off and morphodynamic types of river chan-nels. The results obtained do not contradict on the whole to existent theoretical conceptions concerning this question.
Keywords: 551.4.036(282.247.13)